2014
DOI: 10.3390/rs61010131
|View full text |Cite
|
Sign up to set email alerts
|

Non-Vegetated Playa Morphodynamics Using Multi-Temporal Landsat Imagery in a Semi-Arid Endorheic Basin: Salar de Uyuni, Bolivia

Abstract: Playas in endorheic basins are of environmental value and highly scientific because of their natural habitats of a wide variety of species and indicators for climatic changes and tectonic activities within continents. Remote sensing, due to its capability of acquiring repetitive data with synoptic coverage, provides a unique tool to monitor and collect spatial information about playas. Most studies have concentrated on evaporite mineral distribution using remote sensing techniques but research about grain size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Furthermore, some studies have performed relative correction of atmospherically corrected imagery to account for residual differences between images arising from imperfect preprocessing when surface reflectance is desired (Li et al. ). We suggest this approach only if both comparability between images and surface reflectance units are needed for a particular application.…”
Section: Preprocessingmentioning
confidence: 99%
“…Furthermore, some studies have performed relative correction of atmospherically corrected imagery to account for residual differences between images arising from imperfect preprocessing when surface reflectance is desired (Li et al. ). We suggest this approach only if both comparability between images and surface reflectance units are needed for a particular application.…”
Section: Preprocessingmentioning
confidence: 99%
“…Because of data availability, we selected two sets of satellite images for detailed bank accretion and erosion in the study area (Table 1). The observation period between the two sets of high-resolution satellite images is representative because longer observation periods using relatively long-term time-series satellite data (e.g., Landsat imagery from 1980 to 2011) have shown that changes in channel morphology are ongoing in the study area (Li et al, 2014b). The QuickBird-02 and Worldview-02 images have been projected to Universal Transverse Mercator (UTM).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Although there are no flow gauging records, small to moderate (sub‐bankfull) river flow events occur one or more times in most years, with larger events (bankfull or above) occurring at least once every few years. According to local accounts, following heavy rainfall and significant flow in the Río Colorado and other local rivers, water depths in Salar de Uyuni can reach up to 10 m, but analysis of Landsat time‐series satellite imagery (1985–2011) indicates that the lake typically dries out in the intervening winter months (Li et al, ). Field data on sediment loads are limited, but grain‐size analyses indicate that the lower Río Colorado system is dominated by silt and clay with subordinate very fine sand.…”
Section: Study Areamentioning
confidence: 99%
“…Salar de Uyuni is the world's largest salt lake, and is periodically supplied with water and sediment by low‐gradient, ephemeral rivers such as the Río Colorado. This river has been the focus of extensive previous studies that have shown, inter alia , how high‐resolution satellite imagery can be useful for quantifying channel‐floodplain morphology and dynamics in this poorly or non‐vegetated dryland setting, including meander bend dynamics, the development of crevasse splays, and avulsions (Donselaar et al, ; Torres Carranza, ; Li, , in press; Li et al, , b, , b, ; Li and Bristow, ; Sandén, ). Erosion cells have been noted in the upstream parts of the Río Colorado catchment (Li et al, ) and are also prominent features farther downvalley but have not been investigated in any detail.…”
Section: Introductionmentioning
confidence: 99%